Regulatory role of transcription factor c-Myc in the pathogenesis of psoriasis - Yue Cao; Xu-Ping Niu; Kai-Ming Zhang (PeerJ)
Psoriasis is a chronic relapsing dermatosis characterized by hyperproliferation and poor differentiation of keratinocytes (KCs). The c-Myc gene is one of the main members of the Myc family and exerts multiple biological functions. C-Myc is highly expressed in psoriatic lesions. The co-expressed genes and coexisting factors of c-Myc determine the final survival of cells. The high expression levels of c-Myc in the skin lesions of psoriatic patients are associated with the continuous proliferation of KCs, and form an abnormal state of epidermal dynamics. C-Myc is also involved in the induction of metabolic reprogramming of cells in the development of psoriasis, thus exacerbating the excessive proliferation of psoriatic epidermis. In this review, we focus on the mechanisms of the transcription factor c-Myc in the pathogenesis of psoriasis and its clinical implications.